Knowledge absorption capacity's efficacy to enhance innovation performance through big data analytics and digital platform capability - Adnan Khan; Tao Meng (Journal of Innovation & Knowledge (JIK), 2022)
The 2018 Global Innovation Index ranks Pakistan 118 out of 126 in innovation. One of the main reasons why developing countries, such as Pakistan, fail to innovate is their improvisation of astute and concurrent knowledge. This study explores the contemporary hurdles that lead to manufacturing firms' low agility and innovation performance. Based on the theory of dynamic capability view and the theory of absorptive capacity, we propose that the knowledge absorption capacity of firms can help them organize or utilize dynamic capabilities, such as big data analytics and digital platform capability, to enhance their agility and innovation performance. However, in the presence of a diversified organizational culture (i.e., flexibility orientations and data-driven culture), the desired outcomes may be affected. For this purpose, this study performed a questionnaire survey to collect data for validating the theoretical model. The collected responses from 325 manufacturing firms were analyzed using structural equation modeling, and empirical results reveal a positive relationship between the knowledge absorption capacity, agility, and innovation performance of firms mediated by big data analytics and DP capabilities. Flexibility orientations also showed a significant moderating role, but the role of data-driven culture was not significant. Statistical results reject the hypothesis. This study enriches the scope of the theories mentioned above and comes up with several other interesting theoretical and managerial implications valuable for academicians and policymakers.
Keywords: O3; O32; O31; 650; Innovation performance; Big-data analytics capability; Data-driven culture; DP capability; Firm's agility; Knowledge absorption capacity